2012
DOI: 10.1002/bdd.1826
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive and anti‐angiogenic effects of dietary phenethyl isothiocyanate in an N‐methyl nitrosourea‐induced breast cancer animal model

Abstract: The effect of phenethyl isothiocyanate (PEITC), a component of cruciferous vegetables, on the initiation and progression of cancer was investigated in a chemically induced estrogen-dependent breast cancer model. Breast cancer was induced in female Sprague Dawley rats (8 weeks old) by the administration of N-methyl nitrosourea (NMU). Animals were administered 50 or 150 µmol/kg oral PEITC and monitored for tumor appearance for 18 weeks. The PEITC treatment prolonged the tumor-free survival time and decreased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…This study pointed to the supplementation of isothiocyanates for prolonging the tumor-free survival as well as its chemoprevention in the rats. 28 Additionally, these researchers highlighted that this was the first time it had been reported in a scientific study that an isothiocyanate compound, such as those found in cruciferous vegetables, had anti-angiogenic effects in breast cancer-induced animals. Because a compound with anti-angiogenic effects inhibits the growth of blood vessels, this was a significant finding as a method attesting to the chemopreventative activity of isothiocyanates.…”
Section: Cancer Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…This study pointed to the supplementation of isothiocyanates for prolonging the tumor-free survival as well as its chemoprevention in the rats. 28 Additionally, these researchers highlighted that this was the first time it had been reported in a scientific study that an isothiocyanate compound, such as those found in cruciferous vegetables, had anti-angiogenic effects in breast cancer-induced animals. Because a compound with anti-angiogenic effects inhibits the growth of blood vessels, this was a significant finding as a method attesting to the chemopreventative activity of isothiocyanates.…”
Section: Cancer Researchmentioning
confidence: 99%
“…27 In an animal breast cancer study, progress was made in examining the chemopreventative qualities of isothiocyanates. 28 Breast cancer was induced in eight week old female rats. The rats were administered an isothiocyanate compoundand their tumor appearance was monitored over the course of 18 weeks.…”
Section: Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenethyl isothiocyanate, a naturally occurring isothiocyanate found in some cruciferous vegetables, has cancer prevention effects in breast cancer [234, 235]. Phenethyl isothiocyanate has high bioavailability, and it is likely that phenethyl isothiocyanate undergoes modest first-pass metabolism as metabolites of isothiocyanates can be generated by intestinal as well as hepatic enzymes [236].…”
Section: Natural Products Against Er-positive Breast Cancermentioning
confidence: 99%
“…[234] revealed that phenethyl isothiocyanate exerts chemopreventive effect on the promotion and/or progression stage of DMBA-induced rat mammary carcinogenesis. In addition, phenethyl isothiocyanate reduced the tumor incidence and tumor burden in the NMU-induced breast cancer animal model [235]. McCune et al .…”
Section: Natural Products Against Er-positive Breast Cancermentioning
confidence: 99%